2015
DOI: 10.3892/ol.2015.3159
|View full text |Cite
|
Sign up to set email alerts
|

Horner's syndrome subsequent to minimally invasive video-assisted thyroidectomy in two patients

Abstract: Abstract. Horner's syndrome (HS), characterized by a combination of ptosis and miosis, is an uncommon complication of thyroid surgery, particularly in minimally invasive thyroid surgery. Two cases of HS were observed secondary to minimally invasive video-assisted thyroidectomy in the Department of Thyroid Breast Surgery of Zhejiang Provincial People's Hospital between August 2012 and July 2014. The two patients developed miosis and ptosis following total thyroidectomy; all symptoms had resolved at 1 and 11 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…It is characterized by miosis, ptosis, and anhidrosis, with or without enophthalmia. It may occur after a number of pathologies associated with the cervical region [1][2][3][4][5][6][7] or epidural [8], spinal anesthesia [9], as well as combined spinal-epidural anesthesia [10]. Despite the different techniques for blocking brachial plexus performed by the interscalene [11], transscalene [12], and sometimes, supraclavicular [13,14], and infraclavicular [15] local anaesthetics (LA), could still diffuse via the prevertebral spaces, block sympathetic nerves in the cervical region, as well as also spread to the sympathetic ganglia (the stellate ganglion), and could cause transient characteristic symptoms [16].…”
mentioning
confidence: 99%
“…It is characterized by miosis, ptosis, and anhidrosis, with or without enophthalmia. It may occur after a number of pathologies associated with the cervical region [1][2][3][4][5][6][7] or epidural [8], spinal anesthesia [9], as well as combined spinal-epidural anesthesia [10]. Despite the different techniques for blocking brachial plexus performed by the interscalene [11], transscalene [12], and sometimes, supraclavicular [13,14], and infraclavicular [15] local anaesthetics (LA), could still diffuse via the prevertebral spaces, block sympathetic nerves in the cervical region, as well as also spread to the sympathetic ganglia (the stellate ganglion), and could cause transient characteristic symptoms [16].…”
mentioning
confidence: 99%
“…The most common mechanism of injury of the cervical sympathetic nerve is direct involvement of tumor of inflammation lesions, and the most common sites are prevertebral fascia, paratracheal area, posteromedial area of the carotid sheath, and lung apex [11]. Many studies have reported that Horner syndrome appeared after cervical surgery, but thyroid-surgery associated Horner syndrome is rare [12] [13]. In this report, we presented two typical Horner's syndrome after thyroid surgery.…”
Section: Discussionmentioning
confidence: 74%
“…Horner's syndrome, also known as Bernard-Horner syndrome, is characterized by miosis, ptosis, and apparent enophthalmos with or without anhidrosis. 2 This occurs due to affection of ipsi-lateral sympathetic trunk. 3 Horner's [ ( F i g .…”
Section: Discussionmentioning
confidence: 99%